2020
DOI: 10.1590/1678-4685-gmb-2019-0338
|View full text |Cite
|
Sign up to set email alerts
|

USP7 deubiquitinates and stabilizes EZH2 in prostate cancer cells

Abstract: Regulation of target proteins by the ubiquitin-proteasome system (UPS) is common in a wide range of cellular events, including transcriptional regulation, cell cycle progression, differentiation, and tumorigenesis. Ubiquitinspecific protease 7 (USP7) has been implicated in tumor development and metastasis in various malignancies through the regulation of target protein stability. In this study, we found that the enhancer of zeste homolog 2 (EZH2), which catalyzes the methylation at lysine 27 of histone H3, is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 39 publications
1
32
0
Order By: Relevance
“…On the other hand, we also found that P22077 lead inhibition of invasion and migration in vitro and in vivo in melanoma. Several substrates contribute to invasion and migration regulated by USP7, such as EZH2 in prostate cancer, LSD1 in glioblastoma [38,39]. Contrary, the role of ROS in triggering signaling pathways, such as activation of MAPK, ERK, JNK, and p-38 MAPK via growth factor-mediated stimulation of receptor tyrosine kinases (RTKs) for cell migration and invasion has been well-established [40].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, we also found that P22077 lead inhibition of invasion and migration in vitro and in vivo in melanoma. Several substrates contribute to invasion and migration regulated by USP7, such as EZH2 in prostate cancer, LSD1 in glioblastoma [38,39]. Contrary, the role of ROS in triggering signaling pathways, such as activation of MAPK, ERK, JNK, and p-38 MAPK via growth factor-mediated stimulation of receptor tyrosine kinases (RTKs) for cell migration and invasion has been well-established [40].…”
Section: Discussionmentioning
confidence: 99%
“…As one of the most extensively studied inhibitors, USP7 inhibitors have played an effective and highly specific role in many studies. They have a significant inhibitory effect on tumors ( Lee et al, 2020 ; Leger et al, 2020 ; Ohol et al, 2020 ; Schauer et al, 2020a ). P22077/50429 exerted anti-oncogene function in a variety of malignant tumors ( Fan et al, 2013 ; Zhang W. et al, 2020 ) and improved chemoresistance in pancreatic cancer ( Chen H. et al, 2020 ).…”
Section: Research On Dub Inhibitors and Their Effects On Srss And Taimmentioning
confidence: 99%
“…FT827/671 inhibited tumors by degrading the oncogenic E3 ligase MDM2 ( Turnbull et al, 2017 ). In the latest study, P5091 inhibitors showed robust tumor suppression effects in preclinical models of various tumors ( An et al, 2017 ; Wang et al, 2017 ; Hayal et al, 2020 ; He et al, 2020 ; Lee et al, 2020 ). Among these cancers, in colorectal cancer, P5091 improves the antitumor immune response and reduces the proportion of Tregs in tumor xenografts in mice ( Fu et al, 2019 ).…”
Section: Research On Dub Inhibitors and Their Effects On Srss And Taimmentioning
confidence: 99%
“…We next set out to determine how nuclear p85β stabilizes EZH1 and EZH2 proteins. It has been reported that USP7 deubiquitinates and stabilizes EZH2 in prostate cancer cells 32,33 . We thus postulated that nuclear p85β brings USP7 to EZH1 and EZH2, thereby protecting them from ubiquitin-mediated protein degradation.…”
Section: Nuclear Translocation Of P85 Is Critical For Tumorigenicity Of Pik3ca E545kmentioning
confidence: 99%